Induced unconventional superconductivity on the surface states of Bi2Te3topological insulator - Charpentier, Sophie; Galletti, Luca; Kunakova, Gunta; Arpaia, Riccardo; Song, Yuxin; Baghdadi, Reza; Wang, Shu Min; Kalaboukhov, Alexei; Olsson, Eva; Tafuri, Francesco; Golubev, Dmitry; Linder, Jacob; et al. (Nature Communications, 2017)
Topological superconductivity is central to a variety of novel phenomena involving the interplay between topologically ordered phases and broken-symmetry states. The key ingredient is an unconventional order parameter, with an orbital component containing a chiral px + ipy wave term. Here we present phase-sensitive measurements, based on the quantum interference in nanoscale Josephson junctions, realized by using Bi2Te3 topological insulator. We demonstrate that the induced superconductivity is unconventional and consistent with a sign-changing order parameter, such as a chiral px + ipy component. The magnetic field pattern of the junctions shows a dip at zero externally applied magnetic field, which is an incontrovertible signature of the simultaneous existence of 0 and π coupling within the junction, inherent to a non trivial order parameter phase. The nano-textured morphology of the Bi2Te3 flakes, and the dramatic role played by thermal strain are the surprising key factors for the display of an unconventional induced order parameter.